Impact of Coronavirus Disease (COVID-19) Pandemic on Psychological Well-Being of the Pakistani General Population - Khan, Adeel Ahmed; Lodhi, Fahad Saqib; Rabbani, Unaib; Ahmed, Zeeshan; Abrar, Saidul; Arshad, Saamia; Irum, Saadia; Khan, Muhammad Imran (Frontiers in Psychiatry, 2021)
Background and Objectives: In order to curb the spread of coronavirus disease 2019 (COVID-19), the countries took preventive measures such as lockdown and restrictions of movements. This can lead to effects on mental health of the population. We studied the impact of COVID-19 on psychological well-being and associated factors among Pakistani general population. Methods: An online cross sectional survey was conducted between 26th April and 15th May and included participants from all over the Pakistan. Attitudes and worriedness about COVID-19 pandemic were assessed using a structured questionnaire. A validated English and Urdu version of WHO-5 well-being scale was used to assess the well-being. Factor analysis was done to extract the attitude items domains. Logistic regression was used to assess the factors associated with poor well-being. Results: A total of 1756 people participated in the survey. Almost half 50% of the participants were male and similar proportion was employed. About 41% of the participants were dependent on financial sources other than salary. News was considered a source of fears as 72% assumed that avoiding such news may reduce the fears. About 68% of the population was worried about contracting the disease. The most common coping strategies used during lockdown were; spending quality time with family, eating healthy foods, adequate sleep and talking to friends on phone. Prevalence of poor well-being was found to be 41.2%. Female gender, being unemployed, living in Sindh and Islamabad Capital territory, fear of COVID-19 and having chronic illness were significantly associated with poor well-being. Similarly, coping strategies during lockdown (doing exercise; spending time with family; eating healthy food; having good sleep; contributing in social welfare work and spending time on hobbies) a were also significantly associated with mental well-being. Conclusion: We found a high prevalence 41.2% of poor well-being among Pakistani general population. We also investigated risk factors of poor well-being which included; female gender, unemployment, region, fear, chronic illness and absence of coping strategies. This calls for immediate action at population levels in the form of targeted mass psychological support programs to improve the mental health of population during the COVID-19 crises.